Structural change in Africa misperceptions, new narratives and development in the 21st century - Lopes, Carlos 1960-; Kararach, George (Routledge, Taylor & Francis Group, 2020)
Defining structural transformation -- Seeking transformation? Africa is not alone -- Transformation through industrialization -- Understanding other key enablers of Africa's structural transformation -- Innovative development financing sources -- Selected experiences: drilling into the country dimension -- African circumstances and efforts into the future
Includes bibliographical references and index
Keywords: Wirtschaftsentwicklung; Wandel; Afrika; Strukturwandel / (DE-627)091393264 / (DE-STW)11790-4; Entwicklung / (DE-627)091357322 / (DE-STW)10513-0; Wirtschaftspolitik / (DE-627)091401143 / (DE-STW)10987-4; Afrika / (DE-627)091345790 / (DE-STW)17642-3